2022
DOI: 10.1088/1748-9326/aca77b
|View full text |Cite
|
Sign up to set email alerts
|

Expanding wildland-urban interface alters forest structure and landscape context in the northern United States

Abstract: The wildland-urban interface (WUI), where housing intermingles with wildland vegetation, is the fastest-growing land use type in the United States. Given the ecological and social benefits of forest ecosystems, there is a growing need to more fully understand how such development alters the landscape context and structure of these WUI forests. In a space-for-time analysis we utilized land cover data, forest inventory plots, and housing density data over time to examine differences in forest characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…In addition, the forest AGB estimates for some specific areas are also of interest, such as the wildland-urban interface (WUI) [225]. WUI, where built-up intermingles with wildland vegetation, is the fastest-growing land use type in the United States [226]. Some studies have shown that forest in the WUI had greater carbon storage, with greater aboveground biomass, relative stand density, and more live trees per hectare than non-WUI forest, suggesting a greater capacity to sequester carbon compared to non-WUI forest [226].…”
Section: Uncertainty In Remote Sensing Estimation Of Forest Agbmentioning
confidence: 99%
“…In addition, the forest AGB estimates for some specific areas are also of interest, such as the wildland-urban interface (WUI) [225]. WUI, where built-up intermingles with wildland vegetation, is the fastest-growing land use type in the United States [226]. Some studies have shown that forest in the WUI had greater carbon storage, with greater aboveground biomass, relative stand density, and more live trees per hectare than non-WUI forest, suggesting a greater capacity to sequester carbon compared to non-WUI forest [226].…”
Section: Uncertainty In Remote Sensing Estimation Of Forest Agbmentioning
confidence: 99%
“…En el Este, los bosques de la WUI conservan árboles más grandes y biomasa sobre el suelo que los bosques menos desarrollados, pero con menos diversidad estructural (es decir, los bosques de la WUI tienen menos árboles jóvenes, plántulas y árboles muertos). Esto suscita preocupación por la disminución de la función ecológica, la reducción de la diversidad del hábitat de la vida silvestre y la vulnerabilidad al calentamiento 55 . En el Oeste, la exclusión de los incendios forestales en bosques secos históricamente adaptados a incendios frecuentes ha alterado la estructura y composición de los bosques, lo que ocasiona una mayor carga de combustible en la superficie y en el dosel y aumentando la vulnerabilidad a los incendios forestales de alta severidad 56,57 .…”
Section: Efectos Del Cambio Climático En Los Bosquesunclassified
“…FRAGSTATS software has found extensive application in calculating diverse landscape indices, including fragmentation [30] and diversity [31], enabling analysis and monitoring of the temporal and spatial variations in landscape patterns. Previous studies have demonstrated the effect of patch-level landscape structure on multiple ecosystem services of forests [32,33], which contribute to improving habitat protection and biodiversity [34]. However, the current understanding of the most important drivers behind the BMC of forests at the landscape level has not yet been developed [35,36].…”
Section: Introductionmentioning
confidence: 99%